O regionalności XVII-wiecznych kazań pogrzebowych. Część II: druki poznańskie - Pihan-Kijasowa, Alicja; Motyl, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
In the 17th century funeral sermons were one of the most frequent forms of public utterances. More than 600 funeral sermons were published in Poland at that time. They were issued by publishing houses scattered all over Poland, and thus each region had its representation in this output. Consequently, funeral sermons are a good source for studies into regional differences in the Polish language of the 17th century. The article deals with this problem on the example of Great Polish prints issued in 17th-century Poznań publishing houses of: the Wolrabs, Wojciech Regulus, Wojciech Młodujewicz, Wojciech Laktański, Jan Rossowski, the Printing Office of Lubrański Academy and the Printing Office of SocietatisIesu. The analysis of texts revealed that they manifest the most typical features of the general Polish of that time, but simultaneously the regional features, differential in character (as for example the inflectional suffix -ej of feminine hard-stem nouns: type głowej), as well as frequentative (as for example the exchange of i and y for e before consonants l, ł: type zrobieł). And although the discussed texts were written not only by the authors originating from Great Poland, they are characterized by common linguistic features. Thus, it must be admitted that the employees of printing firms – the editors, proof-readers, typesetters – played a significant role in the final linguistic creation of the 17th-century printed text.